Study of Public Policy in the Development of the Kemaro Island of Palembang - Istianda, Meita; Darmanto, Darmanto; Wahyudi, Heri (Budapest International Research and Critics University, 2021)
The Palembang City Government has an agenda to develop Kemaro Island as a tourist attraction. However, the Palembang city government's agenda has not yet received a positive reaction from the community, especially those involved with the development of Kemaro Island. This study aims to analyze the development of Kemaro Island, Palembang City in the tourism sector through analysis of the Palembang City Government's policy agenda and public perceptions of the Palembang City Government's policy agenda in relation to the development of Kemaro Island as one of the tourism objects in Palembang City.